Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 10 - Review - Page 748: 95



Work Step by Step

$\sqrt 3(\sqrt {27}-\sqrt 3)$ =$\sqrt 3\times\sqrt {27}-\sqrt 3\times\sqrt 3$ =$(\sqrt 3\times\sqrt {9\times3})-(\sqrt 3\times\sqrt 3)$ =$(\sqrt 3\times3\sqrt {3})-(3)$ =$(3\times\sqrt 3\times\sqrt {3})-(3)$ =$3(3)-3$ =$9-3$ =$6$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.